A Targeted Self-Management Approach for Reducing Stroke Risk Factors in African American Men Who Have Had a Stroke or Transient Ischemic Attack. Issue 2 (February 2018) - Sajatovic, Martha; Tatsuoka, Curtis; Welter, Elisabeth; Colon-Zimmermann, Kari; Blixen, Carol; Perzynski, Adam T.; Amato, Shelly; Cage, Jamie; Sams, Johnny; Moore, Shirley M.; Pundik, Svetlana; Sundararajan, Sophia; et al.
Purpose: This study compared a novel self-management (TargetEd MAnageMent Intervention [TEAM]) versus treatment as usual (TAU) to reduce stroke risk in African American (AA) men. Design: Six-month prospective randomized controlled trial with outcomes evaluated at baseline, 3 months, and 6 months. Setting: Academic health center. Participants: Thirty-eight (age < 65) AA men who had a stroke or transient ischemic attack and a Barthel index score of >60 were randomly assigned to TEAM (n = 19) or TAU (n = 19). Intervention: Self-management training, delivered in 1 individual and 4 group sessions (over 3 months). Measures: Blood pressure, glycosylated hemoglobin (HbA1c ), lipids, medication adherence, weight, and standardized measures of health behaviors (diet, exercise, smoking, substances), depression, and quality of life. Qualitative assessments evaluated the perspectives of TEAM participants. Analysis: T tests for paired differences and nonparametric tests. Thematic content qualitative analysis. Results: Mean age was 52.1 (standard deviation [SD] = 7.4) and mean body mass index was 31.4 (SD = 7.4). Compared to TAU, TEAM participants had significantly lower mean systolic blood pressure by 24 weeks, and there was also improvement in HbA1c and high-density lipoprotein cholesterol ( P = .03). Other biomarker and health behaviors were similar between groups. Qualitative results suggested improved awareness of risk factors as well as positive effects of group support.